PaperCAD: A System for Interrogating CAD Drawings Using Small Mobile Computing Devices Combined with Interactive Paper - WeeSan Lee; Thomas F. Stahovich (Advances in Human-Computer Interaction)
Smartphones have become indispensable computational tools. However, some tasks can be difficult to perform on a smartphone because these devices have small displays. Here, we explore methods for augmenting the display of a smartphone, or other PDA, using interactive paper. Specifically, we present a prototype interface that enables a user to interactively interrogate technical drawings using an Anoto-based smartpen and a PDA. Our software system, called PaperCAD, enables users to query geometric information from CAD drawings printed on Anoto dot-patterned paper. For example, the user can measure a distance by drawing a dimension arrow. The system provides output to the user via a smartpen’s audio speaker and the dynamic video display of a PDA. The user can select either verbose or concise audio feedback, and the PDA displays a video image of the portion of the drawing near the pen tip. The project entails advances in the interpretation of pen input, such as a method that uses contextual information to interpret ambiguous dimensions and a technique that uses a hidden Markov model to correct interpretation errors in handwritten equations. Results of a user study suggest that our user interface design and interpretation techniques are effective and that users are highly satisfied with the system.